2003
DOI: 10.1097/01.pep.0000083121.26982.1d
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Neuromuscular Electrical Stimulation Home Program on Impairments and Functional Skills of a Child with Spastic Diplegic Cerebral Palsy: A Case Report

Abstract: These findings indicate that NMES was an effective therapeutic technique to improve strength and motor function of a child with spastic diplegic CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…Improvements in hamstring spasticity and lower limb function,5 and quadriceps–hamstring co-contraction,19 have been recorded through an extended period of quadriceps exercise stimulation. Khalili and Hajihassanie18 also found improvements in hamstring spasticity (and passive knee extension) when stimulation of the quadriceps was added to a passive stretching regime, however, they considered the change for the experimental group as a whole not to be clinically relevant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in hamstring spasticity and lower limb function,5 and quadriceps–hamstring co-contraction,19 have been recorded through an extended period of quadriceps exercise stimulation. Khalili and Hajihassanie18 also found improvements in hamstring spasticity (and passive knee extension) when stimulation of the quadriceps was added to a passive stretching regime, however, they considered the change for the experimental group as a whole not to be clinically relevant.…”
Section: Methodsmentioning
confidence: 99%
“…While four lower limb reviews have been published to date in MEDLINE-cited journals on the use of NMES for CP, only Kerr et al 1 and Merrill3 have also reviewed concurrently the important topic of upper limb applications of NMES. The present review is timely because a number of studies relevant to the scope of this paper were not analysed in the reviews by Kerr et al 1 525 or Merrill 3 6 9 11 14 1618 23 2628. Moreover, the nature of this review as being a succinct clinically oriented analysis differs from Merrill's review, which was a preface to an extended discussion of potential future technological developments.…”
Section: Introductionmentioning
confidence: 94%
“…And found that both groups were improved equally in strength. Daichman et al [11] did a study on the effect of NMES home program on impairments and functional skills of a child with spastic diplegic CP to examine the effects of neuromuscular electrical stimulation (NMES) on impairments and functional skills of a 13-yearold child with spastic diplegic cerebral palsy (CP). NMES was administered to the right quadriceps muscles every other day for six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Preferred speed is often an outcome variable to determine the effectiveness of interventions [10][11][12]. Several gait parameters, however, are speed dependent [13] and analyzing gait parameters at a defined walking speed has been suggested [14,15].…”
Section: Introductionmentioning
confidence: 99%